Biotic and Abiotic Stress Factors Induce Microbiome Shifts and Enrichment of Distinct Beneficial Bacteria in Tomato Roots - Burkhardt Flemer; Sneha Gulati; Alessandro Bergna; Manuela Rändler; Tomislav Cernava; Katja Witzel; Gabriele Berg; Rita Grosch (Phytobiomes Journal, 2022)
Crops are often simultaneously threatened by abiotic and biotic stress factors but the stress response of the plant holobiont is not well understood, despite the high importance of this response to ensure future plant production. Therefore, the aim of this study was to assess the impact of individual and combined abiotic (ionic and osmotic) and biotic (Verticillium dahliae and Fusarium oxysporum) stress factors on plant performance and on the bacterial composition of the root endosphere in tomato. Structure and function of the microbiota was analyzed by 16S ribosomal RNA gene amplicon sequencing and a complementary cultivation approach, including in vitro and in vivo assays. Under all stress conditions, tomato growth and photosynthetic activity was reduced. Combined abiotic stressors with F. oxysporum but not with V. dahliae infection led to an additive negative effect on plant performance. All stress conditions induced a microbiome shift, and changed the relative abundance of phyla such as Firmicutes and classes of Proteobacteria. Endophytes identified as Bacillus, Paenibacillus, and Microbacterium spp. showed tolerance to abiotic stress conditions and plant beneficial effects. Stressor-specific enrichments of beneficial bacteria in the root were discovered (e.g., Paenibacillus in roots infected with F. oxysporum and Microbacterium in roots infected with V. dahliae). Interestingly, endophytes that were able to promote plant growth were obtained only from roots exposed to individual biotic and combined abiotic and biotic stress conditions but not individual abiotic stressors. Our study revealed stressor-specific enrichment of beneficial bacteria in tomato roots, which has implications for novel plant protection strategies.